Laparoscopic sleeve gastrectomy for morbid obesity in renal transplantation candidates: a matched case–control study. (31st May 2020) - Gaillard, Martin; Tranchart, Hadrien; Beaudreuil, Séverine; Lebrun, Amandine; Voican, Cosmin Sebastian; Lainas, Panagiotis; Courie, Rodi; Perlemuter, Gabriel; Parier, Bastien; Hammoudi, Yacine; Durrbach, Antoine; Dagher, Ibrahim
Abstract: Obesity has become an important issue in patients with end‐stage renal disease (ESRD). Since it is considered a relative contraindication for renal transplantation, bariatric surgery has been advocated to treat morbid obesity in transplant candidates, and laparoscopic sleeve gastrectomy (LSG) is the most reported procedure. However, comparative data regarding outcomes of LSG in patients with or without ESRD are scarce. Consecutive patients with ESRD ( n  = 29) undergoing LSG were compared with matched patients with normal renal function undergoing LSG in a 1:3 ratio using propensity score adjustment. Data were collected from a prospective database. Eligibility for transplantation was also studied. A lower weight loss (20 kg (16–30)) was observed in patients with ESRD within the first year as compared to matched patients (28 kg (21–34)) ( P  < 0.05). After a median follow‐up of 30 (19–50) months in the ESRD group, contraindication due to morbid obesity was lifted in 20 patients. Twelve patients underwent transplantation. In patients with ESRD potentially eligible for transplantation, LSG allows similar weight loss in comparison with matched patients with normal renal function, enabling lifting contraindication for transplantation due to morbid obesity in the majority of patients within the first postoperative year.